Simultaneous determination of eight major bioactive compounds in Dachengqi Tang (DT) by high-performance liquid chromatography - Chen Guanyuan; Zhu Zhengyan; Wan Meihua; Tang Wenfu; Huang Xi (BMC, 2008)
Abstract Background Dachengqi Tang (DT) is a common traditional Chinese medicine formula for expelling neire ('internal heat') in the stomach and intestines. There was no reliable analytical method available for the quality control of DT. Methods A high-performance liquid chromatography (HPLC) method with a reverse phase C18 column (150 × 4.6 mm) was developed. The mobile phase was methanol with 0.2% acetic acid. Eight markers including naringin, hesperidin, aloe emodin, rhein, honokiol, magnolol, emodin and chrysophanol were determined. Results Regression analysis revealed a linear relationship between the concentrations of the markers and the peak area ratio of the standards and internal standard. The limit of detection (S/N = 3) and the limit of qualification (RSD < 20%) ranged from 0.21 to 0.43 ng/μl and 0.76 to 1.74 ng/μl respectively. The recovery was between 95.6% and 103.4%. The tests on the samples from three batches of DT showed that the profiles of the markers did not vary significantly among batches. Conclusion A reliable HPLC method for simultaneous determination of the eight markers in DT was developed.